PERBEDAAN PENGGUNAAN METODE WAHDAH DAN TALAQQI TERHADAP KECEPATAN MENGHAFAL AL-QUR’AN - Muhammad Ilyas (P3M STAI MIFTAHUL ULUM LUMAJANG, 2023)
Talking about the Qur’an, the Qur’an is the most noble and special holy book of Islam. TheQur'an functions as a provider of explanation, as a defender between what is true and false,and as a guide to the truth. The Qur'an also functions as the main source of Islamic teachingswhich contain the values of aqidah, morals, sharia and mu'amalah. One of the noble effortsthat must be made by humanity to maintain the authenticity and purity of the Qur’an is bypracticing and memorizing it properly and correctly. In memorizing the Qur'an, you need toknow what methods are effective to apply to memorizing the Qur'an. In this research, themethod that will be studied is the difference in the use of the Wahdah and Talaqqi methodson the speed of memorizing the Qur’an.This research used an experimental method with the research population, namely allstudents at Al-Miftah Silo Middle School with a total of 89 students. The research sampleuses techniquessaturated sampling that is, the entire research population is used as theresearch sample. Data collection used questionnaires and interviews with supervisingteachers and students, and the data analysis technique used the Chi Square formula (X2).The results of the research show that: 1) There is no difference in the use of the wahdahmethod and the talaqqi method on the speed of memorizing the Qur'an with results X2O0.33 and X2t at a significance level of 5% = 3.841 Thus tcount < ttable (0.33 > 3.841). 2) There isno difference in the use of the wahdah method on the speed of memorizing the Koran withresult X2O smaller than X2t (3.24< 3.841). 3) There is a difference in the use of the Talaqqimethod on the speed of memorizing the Koran with X results2O greater than X2t (5,339 >3,841)